Neurological effects of fat embolism syndrome: A case report. (November 2017) - Shacklock, Emma; Gemmell, Andrew; Hollister, Nigel
Fat embolism syndrome is a serious multi-system pathology which classically affects the respiratory system, neurological system and causes a petechial rash. We present the case of a 20-year-old farmer who developed fat embolism syndrome following a traumatic femoral fracture. Features developed within 24 h of injury and necessitated a prolonged stay in Intensive Care. He exhibited significant signs of cerebral fat embolism syndrome including coma and seizures but went on to make full functional recovery. Magnetic resonance imaging is the recommended imaging modality for patients with suspected cerebral fat embolism. In this case, computerised tomography was inconclusive, but magnetic resonance imaging demonstrated the "starfield pattern" of multiple high signal foci on a dark background. Supportive treatment of fat embolism syndrome is required in an appropriate setting, such as High Dependency or Intensive Care, for patients at risk of hypoxia or neurological deterioration. Despite major neurological involvement of fat embolism syndrome, full recovery is described by several cases including ours.